Analisis Pengaruh Konfigurasi Mata Pisau Pada Mesin Pencacah Sederhana Terhadap Kualitas Cacahan Material Pla dan Pet - Fikri, Muhammad Luqman Saiful; Saleh, Yasya Khalif Perdana; Mulyono, Sidik; Danu , Ahmad (KOLECER Scientific Journal of Mechanical Engineering, 2025)
In everyday life, both organic and inorganic waste remain persistent problems, with plastic waste being a significant environmental concern in Indonesia. According to the Ministry of Environment and Forestry, the national waste volume in 2021 was estimated at 68.5 million tons. Although most plastics are recyclable, efficient recycling depends on proper size reduction mechanisms. Polyethylene terephthalate (PET) is one of the most commonly used plastics, and polylactic acid (PLA) is also increasingly applied due to its biodegradable properties. However, there is a lack of comparative studies on blade design performance for shredding different plastic types. This study aims to develop a plastic shredder capable of processing PET, PLA, and their mixtures, and to evaluate the effect of three blade configurations—straight, zig-zag, and wave—on particle size outcomes. Experimental testing revealed that straight blades produced the largest average particle sizes: 5.63 mm for PET and 5.04 mm for PLA. Zig-zag blades yielded the smallest sizes: 4.70 mm for PET and 2.36 mm for PLA. The wave blade configuration produced intermediate results: 5.60 mm for PET and 4.17 mm for PLA. PLA consistently resulted in smaller particles than PET across all configurations. The zig-zag blade design proved most effective for fine shredding, particularly for PLA material. These results highlight the importance of blade geometry in optimizing shredding performance and plastic recyclability. This research provides insights for the development of efficient, small-scale recycling machines tailored to different plastic types and offers a practical approach for reducing plastic waste in local communities